STRATEGI PENINGKATAN PELAYANAN PUBLIK DI KOTA BEKASI DALAM RANGKA MENINGKATKAN KESEJAHTERAAN MASYARAKAT - Indrijantoro, Widodo; Irwansyah, Iwan (Jurnal Ilmu Administrasi Publik, 2025)
This study aims to analyze strategies for improving public services in Bekasi City in order to improve public welfare. Quality public services are one of the key factors in achieving public welfare, because effective and efficient services can improve the quality of life of the community. This study uses a qualitative approach with a descriptive analytical method, involving in-depth interviews, observations, and documentation analysis to identify the strategies that have been implemented and the challenges faced in public services in Bekasi City. The results of the study indicate that although there have been several efforts to improve the quality of service, such as digitalization of services and infrastructure improvements, there are still obstacles in the form of lack of coordination between agencies, limited human resources, and low levels of public participation in service evaluation. Therefore, a more integrated strategy is needed, increased training for service officers, and increased communication between the government and the community. With the implementation of these strategies, it is hoped that more efficient, responsive, and accountable public services can be created, which in turn can improve the welfare of the Bekasi City community.